Natural convection in Polar Enclosure / R. A. Rasih...[et al.] - R. A., Rasih; Ahmad Bakir, Azman; Zubair, Ahmad Faiz; Abdul Latif, Mohd Noor Halmy (2014)
Natural convection in fluid-filled, 2D cylindrical sector enclosure heated from below and cooled from above is studied numerically for a wide variety of Rayleigh number. A numerical model by using finite difference method with first order upwind was chosen for the solution of the mass, momentum and energy transfer governing equations. Stream-vorticity function is applied in order to reduce the pressure term in momentum equation. Simulations are performed for several values of both the length in radial direction with angle direction ratio of the enclosure in the range between (19/16)π to (19/4)π, and the Rayleigh number based on the angle of enclosure in the range between 102 to 106. These parameters influence upon the flow patterns, the temperature distributions and the heat transfer rates. Rayleigh number afftected the natural convection process by increase the heat transfer rate from hot temperature to cold temperature.